The Influence of Self-Regulation on Learner’s Behavioral Intention to Reuse E-Learning Systems: A Moderated Mediation Model - Xu, Jia; Qiu, Xiaoyan (Frontiers in Psychology, 2021)
Learners’ behavioral intention to reuse e-learning is of great significance to the implementation and management of e-learning in higher education. This study examined the relationship between self-regulation and behavioral intention to reuse by focusing on the mediating role of study engagement and the moderating role of peer collaboration. Based on a sample of 379 undergraduates from central China, we found that self-regulation positively influences behavioral intention to reuse via study engagement. In addition, moderated path analysis indicated that peer collaboration strengthened the direct effect of self-regulation on study engagement and its indirect effect on behavioral intention to reuse. Theoretical and practical implications of these findings are discussed as well.